Enhanced Memory for both Threat and Neutral Information Under Conditions of Intergroup Threat - Zhu, Yong; Zhao, Yufang; Ybarra, Oscar; Stephan, Walter G.; Yang, Qing (Frontiers in Psychology, 2015)
Few studies have examined the effect of intergroup threat on cognitive outcomes such as memory. Different theoretical perspectives can inform how intergroup threat should affect memory for threat-relevant and neutral information, such as the mood-congruency approach, Yerkes-Dodson law, Easterbrook’s theory, and also evolutionary perspectives. To test among these, we conducted two experiments to examine how exposure to intergroup threats affected memory compared to control conditions. In study 1, we manipulated symbolic threat and examined participants’ memory for threat and neutral words. In study 2, memory performance was assessed following the induction of realistic threat. Across the studies, in the control condition participants showed better memory for threat-related than neutral information. However, participants under threat remembered neutral information as well as threat-related information. In addition, participants in the threat condition remembered threat-related information as well as participants in the control condition. The findings are discussed in terms of automatic vigilance processes but also the effects of threat on arousal and its effect on information processing. This latter perspective, suggests paradoxically, that under some circumstances involving an outgroup threat, non-threatening information about outgroups can be extensively processed.